Jurnal Sedina Ning UCIC: Inovasi Edukatif Untuk Membangun Budaya Berbagi Pengetahuan di Kalangan Calon Mahasiswa Baru - Oktaviani, Indri; Marselia, Rosa; Asfi, Marsani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2025)
The Sedina Ning UCIC program is a new approach in student orientation activities aimed at fostering a culture of knowledge sharing among incoming university students. This initiative emphasizes active participation through a series of educational activities such as group discussions, digital learning simulations, interactive games, and sharing sessions with lecturers and senior students. Implemented using a social constructivist approach, the program consists of three main phases: planning, implementation, and evaluation. Observations during the program indicate a high level of engagement among participants, as well as improved understanding of academic values and the importance of building social relationships within the campus environment. Evaluation through participant feedback also revealed that the program effectively supported students’ adaptation to university life. Based on these outcomes, the program is considered a strong model for orientation activities that integrate educational values with student involvement.